Program and service management at Universiti Utara Malaysia: how satisfied are the graduates? / Reynaldo Gacho Segumpan and Joanna Soraya Abu Zahari - Segumpan, Reynaldo Gacho; Joanna Soraya Abu Zahari (ACRULeT, Faculty of Education & UiTM Press, 2006)
This descriptive research dealt with the programme and service satisfaction of graduates in terms of (1) Curriculum, (2) Career and Counseling Services, (3) Teaching Staff, and (4) Facilities at Universiti Utara Malaysia. Differences in satisfaction were also ascertained when the respondents were grouped by demographic characteristics such as gender, ethnicity, entry qualification, field of study, and work status. Data were gathered using a survey questionnaire and analyzed using descriptive and inferential statistics via the SPSS at 0.05 significance level. Findings showed that, overall, the respondents were satisfied most with Facilities, followed by Curriculum and Teaching Staff, and then Career and Counseling Services. “Library” was rated the highest for Facilities, “inculcation of positive values” for Curriculum, “qualifications” for Teaching Staff, and “information on job and career opportunities and further studies” for Career and Counseling Services. There were significant differences in the respondents’ satisfaction across the four components when grouped by demographic characteristics. Recommendations are offered and the implications of the findings are discussed.